2016
DOI: 10.3109/03009742.2016.1141979
|View full text |Cite
|
Sign up to set email alerts
|

Long-term drug survival of biological agents in patients with rheumatoid arthritis in clinical practice

Abstract: After several years of BA treatment in clinical practice, the survival rate was low, mainly as a result of ADRs and inefficacy. We also found differences between the discontinuation rates of BAs and other clinical factors that modify their survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 13 publications
0
16
0
1
Order By: Relevance
“…Patients with RA tend to discontinue treatment with bDMARDs mainly because of AEs and lack or loss of clinical efficacy , with a similar proportion of LTE patients discontinuing because of AEs and lack of efficacy . Discontinuations that are due to lack/loss of efficacy with tofacitinib were low (3.6%) compared with LTE studies of bDMARDs used in the treatment of RA (8%–23%) .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Patients with RA tend to discontinue treatment with bDMARDs mainly because of AEs and lack or loss of clinical efficacy , with a similar proportion of LTE patients discontinuing because of AEs and lack of efficacy . Discontinuations that are due to lack/loss of efficacy with tofacitinib were low (3.6%) compared with LTE studies of bDMARDs used in the treatment of RA (8%–23%) .…”
Section: Discussionmentioning
confidence: 94%
“…A systematic review of studies from clinical practice indicated that the persistence of golimumab therapy (2‐year drug survival rates ranging from 40% to 77%) may be higher than for other TNFis . In a longitudinal observational study of patients with RA receiving bDMARDs between 1999 and 2013, discontinuations were mainly due to AEs (45.8%) and lack of efficacy (40.8%) . Similarly, an analysis of registry data for patients with RA treated with rituximab, infliximab, or etanercept also identified inadequate response (IR) to treatment (41.4%) and occurrence of serious AEs (22.2%) as the main reasons for discontinuation of these treatments .…”
Section: Introductionmentioning
confidence: 99%
“…We have been interested in achieving clinical effects similar to those achieved with the TNF α biologicals, but with small molecules, to address issues of immunogenicity (12, 13), supply chain complexity (14), health economics, and other indications e.g., a TNF α inhibitor with an anti-amyloid β could slow the progression of Alzheimer’s disease (15). The opportunity to fine-tune TNF α biology with small molecules could also increase the therapeutic safety window over infection risk.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 70 included studies, 19 were full-text articles, 7,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] while 51 were conference abstracts. Study characteristics are described in Supplementary Table 6.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Among the studies including patients with IA, 21 studies included some form of PRO, 18,20,21,23,24,27,[29][30][31]36,48,49,54,57,59,65,75,77,78,80,84 of which 10 studies reported PROs prior to the switch only and therefore did not provide any information on the patient experience of switching treatment. 20,21,23,24,[29][30][31]49,59,78 The PRO measurement tools used are summarized in Figure 3.…”
Section: Indirectly Reported Patient Experience Of Switchingmentioning
confidence: 99%